Melatonin reduces proliferation and promotes apoptosis of bladder cancer cells by suppressing O‐GlcNAcylation of cyclin‐dependent‐like kinase 5. Issue 3 (18th September 2021) - Wu, Jinpeng; Tan, Zengqi; Li, Hongjiao; Lin, Meixuan; Jiang, Yazhuo; Liang, Liang; Ma, Qilong; Gou, Junjie; Ning, Lulu; Li, Xiang; Guan, Feng
Abstract: Melatonin helps to maintain circadian rhythm, exerts anticancer activity, and plays key roles in regulation of glucose homeostasis and energy metabolism. Glycosylation, a form of metabolic flux from glucose or other monosaccharides, is a common post‐translational modification. Dysregulated glycosylation, particularly O‐GlcNAcylation, is often a biomarker of cancer cells. In this study, elevated O‐GlcNAc level in bladder cancer was inhibited by melatonin treatment. Melatonin treatment inhibited proliferation and migration and enhanced apoptosis of bladder cancer cells. Proteomic analysis revealed reduction in cyclin‐dependent‐like kinase 5 (CDK5) expression by melatonin. O‐GlcNAc modification determined the conformation of critical T‐loop domain on CDK5 and further influenced the CDK5 stability. The mechanism whereby melatonin suppressed O‐GlcNAc level was based on decreased glucose uptake and metabolic flux from glucose to UDP‐GlcNAc, and consequent reduction in CDK5 expression. Melatonin treatment, inhibition of O‐GlcNAcylation by OSMI‐1, or mutation of key O‐GlcNAc site strongly suppressed in vivo tumor growth. Our findings indicate that melatonin reduces proliferation and promotes apoptosis of bladder cancer cells by suppressing O‐GlcNAcylation of CDK5.